2007
DOI: 10.3354/meps07031
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of carbon, nitrogen and oxygen cycles in sediments from a Mediterranean lagoon: a seasonal perspective

Abstract: International audienceExperimental data and simulations were used to investigate the seasonal coupling between carbon, nitrogen and oxygen cycles in marine sediments from a eutrophic shallow lagoon in the Mediterranean Sea area. A negative seasonal correlation was observed between oxygen consumption and coupled nitrification–denitrification rates in surface sediments. Elevated values of oxygen consumption rates were reached during warm periods (up to 87.7 mmol m–2 d–1) whereas nitrification and denitrification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 45 publications
11
19
0
Order By: Relevance
“…Model results showed that organic matter accumulation in the farming area enhanced the anaerobic metabolism. Oxygen microprofiles recorded by Dedieu et al (2007) inside and outside the mussel farm presented differences which are comparable to those recorded in the present work, with a decrease of 50 % in oxygen penetration depth, and an increase up to 3 times of diffusive O 2 fluxes (30 mmol O 2 m −2 d −1 versus 90 mmol O 2 m −2 d −1 ). In Dedieu et al (2007) this was accompanied by a remarkable enhancement in NH + 4 concentrations, which was not visible in the field data reported in the present study.…”
Section: Influences Of Perturbed Poc Fluxes On Organic Matter Mineralsupporting
confidence: 72%
See 4 more Smart Citations
“…Model results showed that organic matter accumulation in the farming area enhanced the anaerobic metabolism. Oxygen microprofiles recorded by Dedieu et al (2007) inside and outside the mussel farm presented differences which are comparable to those recorded in the present work, with a decrease of 50 % in oxygen penetration depth, and an increase up to 3 times of diffusive O 2 fluxes (30 mmol O 2 m −2 d −1 versus 90 mmol O 2 m −2 d −1 ). In Dedieu et al (2007) this was accompanied by a remarkable enhancement in NH + 4 concentrations, which was not visible in the field data reported in the present study.…”
Section: Influences Of Perturbed Poc Fluxes On Organic Matter Mineralsupporting
confidence: 72%
“…Oxygen microprofiles recorded by Dedieu et al (2007) inside and outside the mussel farm presented differences which are comparable to those recorded in the present work, with a decrease of 50 % in oxygen penetration depth, and an increase up to 3 times of diffusive O 2 fluxes (30 mmol O 2 m −2 d −1 versus 90 mmol O 2 m −2 d −1 ). In Dedieu et al (2007) this was accompanied by a remarkable enhancement in NH + 4 concentrations, which was not visible in the field data reported in the present study. This can certainly be related to the difference in the rate of biodeposit accumulation, although other factors can also play a role (changes of local macrobenthic activity and of coupled nitrification-denitrification rates).…”
Section: Influences Of Perturbed Poc Fluxes On Organic Matter Mineralsupporting
confidence: 72%
See 3 more Smart Citations